The impact of executive environmental background on corporate environmental information disclosure - Wang, Ruolin (Transactions on Economics, Business and Management Research, 2024)
With the rapid development of the economy, environmental problems are becoming increasingly serious, and the importance of environmental information disclosure is particularly prominent. Environmental information disclosure, as a direct channel for investors, is deeply influenced by board secretaries or investor relations liaison officers. This article analyzes the mechanism by which the environmental background of the executive secretary affects the quality of corporate environmental information disclosure, as well as the moderating effect of external supervision such as environmental regulations and media attention, and proposes corresponding hypotheses. This article selects A-share listed companies from 2008 to 2022 as samples to empirically test the research hypothesis. The main conclusion of this article is as follows: there is a significant positive correlation between the environmental background of the board secretary and the quality of corporate environmental information disclosure. Based on the conclusions drawn, this article proposes corresponding policies and management recommendations, analyzes the limitations and shortcomings of the research, and looks forward to future research directions.